REKONSEPSI PENGECUALIAN MONOPOLI YANG DISELENGGARAKAN OLEH BADAN USAHA MILIK NEGARA DALAM HUKUM PERSAINGAN USAHA DI INDONESIA - Puspitasari, Zuhro (Jurnal Panorama Hukum, 2017)
The purpose of this paper is to formulate the reconception of exceptions of monopolistic practices organized by SOEs (state-owned enterprises). This normative juridical study using the approach of legislation and conceptual approach. The result of his research is that there are some things that should be considered in terms of reconciliation of monopoly parktik exceptional conducted by SOEs. Based on the aforementioned matters, the authors formulate the reconception of the exception of monopolistic practices organized by the SOEs, which read as follows: (1) The acts or actions held by SOEs and / or bodies and / or institutions established or appointed by the Government based on legislation. (2) Further provisions as referred to in paragraph (1) shall be regulated by law.